PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PENGURUS PONDOK (PP. Nurul Jadid Paiton Probolinggo) - Adi usmanto; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT        The purpose of this study was to determine the effect of transformational leadership motivation and organizational commitment on the performance of Nurul Jadid Islamic Boarding School administrators. The research method used descriptive quantitative analysis with a sample of 66 administrators of Nurul Jadid Islamic Boarding School and multiple linear regression analysis tools with SPSS 20. The results obtained in this study were transformational leadership positively influencing the performance of boarding school Nurul Jadid Paiton Probolinggo, Motivation did not have a significant effect on the performance of the management of Nurul Jadid Paiton Probolinggo Islamic Boarding School, Organizational Commitment had no significant effect on the performance of Nurul Jadid Paiton Probolinggo Islamic Boarding School administrators.Keywords: management performance, transformational leadership, motivation, organizational commitment